Fluid characteristics from shallow magmatic environments: A contribution to danburite bearing Luc Yen pegmatites, northern Vietnam - Krenn, Kurt; Huong, Le Thi Thu (Vietnam Journal of Earth Sciences, 2019)
Danburite as a member of the Luc Yen pegmatite mineral assemblage has been studied using fluid inclusion microthermometry and Raman spectroscopy. Data characterize well-preserved fluid inclusions which originate from primary large tubular inclusions as result of necking down. Same modifications underwent a second inclusion generation that evolved during healing of a later crack. Both generations of fluid inclusions show the same chemistry (H2O-CO2) characterizing 3-phase inclusions with additional solids (calcite, sassolite and danburite). Inclusions consist of pure CO2 and H2O with additional NaCl ± KCl comprising a salinity of about 4.5 mass%. Internal fluid inclusion pressures as well as bulk inclusion densities have been calculated using the fermi diad split method of pure CO2 at clathrate melting temperatures of the system and total homogenization temperatures, respectively. Mean internal pressures of ca. 4.5 MPa as well as a bulk density around 0.60 g/cm3 represent a low-dense fluid with XH2O 0.86 and XCO2 0.14 in composition that was present during formation of danburite. Data characterize danburite as a late stage crystallization member of the pegmatite in a shallow magmatic environment. References Anovitz L.M. and Grew, E.S., 1996. Mineralogy, petrology and geochemistry of boron: An introduction. In L.M. Anovitz and E.S. Grew, Eds., Boron: Mineralogy, Petrology, and Geochemistry, Reviews in Mineralogy, Vol. 33, Mineralogical Society of America, Washington DC, USA, 1–40. Bakker, R.J., 1997. Clathrates: computer programs to calculate fluid inclusion V–X properties using clathrate melting temperatures. Computer & Geosciences, 23, 1-18. Bakker R.J., Diamond L.W., 2000. Determination of the composition and molar volume of H2O–CO2 fluid inclusions by microthermometry. Geochimica et Cosmochimica Acta, 64, 1753-1764. Bodnar R.J., 1993. Revised equation and table for determining the freezing point depression of H2O-NaCl solutions. Geochimica et Cosmochimica Acta, 57, 683-684. Chauviré B., Rondeau B., Fritsch E., Ressigeac P., Devidal J.-L., 2015. Blue spinel from the Luc Yen District of Vietnam. Gems & Gemology, 51, 1, 2–17. Diamond L., 2003. Glossary: Terms and symbols used in fluid inclusion studies, In: Samson, I., Anderson, A., Marshall, D. (Eds.), Fluid Inclusions: Analysis and Interpretation. Mineralogical Association of Canada Short Course Series, 32, 365-374. Duan Z., Møller N., Weare J.H., 1996. A general equation of state for supercritical fluid mixtures and molecular dynamics simulation of mixture PVTX properties. Geochimica et Cosmochimica Acta, 60, 1209-1216. Davis D.W., Lowenstein T.K., Spencer R.J., 1990. Melting behavior of fluid inclusions in laboratory-grown halite crystals in the systems NaCl-H2O, NaCl-KCl-H2O, NaCl-MgC12-H2O, and NaCl-CaCl2-H2O. Geochimica et Cosmochimica Acta, 54, 591-601. Fall A., Tattrich B., Bodnar R.J., 2011. Combined microthermometric and Raman spectroscopic technique to determine the salinity of H2O-CO2-NaCl fluid inclusions based on clathrate melting. Geochimica et Cosmochimica Acta, 75, 951-964. Garnier V., Ohnenstetter D., Giuliani G., Maluski H., Deloule E., Phan Trong T., Pham Van L., Hoang Quang V., 2005. Age and significance of ruby bearing marble from the Red River shear zone, northern Vietnam. Canadian Mineralogist, 43(4), 1315-1329. Goldstein R.H., Reynolds T.J., 1994. Systematics of fluid inclusions in diagenetic minerals. SEPM Short Course, 31. Kurshakova L.D., 1982. Temperature regime and geochemical conditions of formation of danburite. International Geology Review 24, 3, 367–371. Roedder E. 1984. Fluid Inclusions. Reviews in Mineralogy, 12, 646. Tattitch B.C., Candela P.A., Piccoli P.M., Bodnar R.J., 2015. Copper partitioning between felsic melt and H2O-CO2 bearing saline fluids. Geochim.